Autoantibody repertoire characterization provides insight into the pathogenesis of monogenic and polygenic autoimmune diseases - Clarke, Thomas; Du, Pan; Kumar, Satyendra; Okitsu, Shinji L.; Schuette, Mark; An, Qi; Zhang, Jinyang; Tzvetkov, Evgeni; Jensen, Mark A.; Niewold, Timothy B.; Ferre, Elise M. N.; Nardone, Julie; et al. (Frontiers in Immunology, 2023)
Autoimmune diseases vary in the magnitude and diversity of autoantibody profiles, and these differences may be a consequence of different types of breaks in tolerance. Here, we compared the disparate autoimmune diseases autoimmune polyendocrinopathy–candidiasis–ecto-dermal dystrophy (APECED), systemic lupus erythematosus (SLE), and Sjogren’s syndrome (SjS) to gain insight into the etiology of breaks in tolerance triggering autoimmunity. APECED was chosen as a prototypical monogenic disease with organ-specific pathology while SjS and SLE represent polygenic autoimmunity with focal or systemic disease. Using protein microarrays for autoantibody profiling, we found that APECED patients develop a focused but highly reactive set of shared mostly anti-cytokine antibodies, while SLE patients develop broad and less expanded autoantibody repertoires against mostly intracellular autoantigens. SjS patients had few autoantibody specificities with the highest shared reactivities observed against Ro-52 and La. RNA-seq B-cell receptor analysis revealed that APECED samples have fewer, but highly expanded, clonotypes compared with SLE samples containing a diverse, but less clonally expanded, B-cell receptor repertoire. Based on these data, we propose a model whereby the presence of autoreactive T-cells in APECED allows T-dependent B-cell responses against autoantigens, while SLE is driven by breaks in peripheral B-cell tolerance and extrafollicular B-cell activation. These results highlight differences in the autoimmunity observed in several monogenic and polygenic disorders and may be generalizable to other autoimmune diseases.